Sosialisasi Resiko Paparan Radiasi Gelombang Elektromagnetik yang dihasilkan oleh Smartphone terhadap Pertumbuhan Otak Anak - Ayu Berlianti, Nindha; Hayati, Nur; Af’idah, Noer; Manasikana, Oktaffi Arinna; Wijayadi, Andri Wahyu (Jurnal Pemberdayaan Masyarakat, 2021)
This community service program aimed to increase the knowledge and awareness of mothers in Sumbernongko Village, Ngusikan District, Jombang Regency about the importance of early education about the risks and dangers of electromagnetic waves exposed by smartphone signals (gadgets). The activities in this program were carried out by giving lectures, presenting interactive videos and question and answer. The first step was to provide education about what radiation is and its use in communication and the impacts that will occur in the short and long term. Then, it was followed by giving tips on reducing the use of gadgets. The target of this community service program was to make parents able to be wise and firm when limit ing the use of gadgets to their children and familiarize their children with activities outside or inside the home more because the role of parents in children's development is largely determined by their daily activities.